2017
DOI: 10.1097/md.0000000000007461
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of thyroid lobectomy for unilateral multifocal papillary carcinoma

Abstract: The National Comprehensive Cancer Network (NCCN) guidelines recommend completion thyroidectomy for patients with multifocal papillary thyroid carcinoma (PTC) diagnosed by paraffin pathology after lobectomy. However, studies for the influence of surgical range on prognosis of unilateral multifocal carcinoma are scarce. We analyzed the clinicopathological characteristics and long-term outcomes of patients with unilateral multifocal PTC to identify risk factors for recurrence and disease-related death.The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…Many studies had noted that pathological factors that necessitate completion thyroidectomy includes multifocality, extrathyroidal extension, and some studies also quote the size of the nodule [12,13]. In our study, it was noted that patients with age more than 55 years 6.67 times increased risk of malignancy compared to middle age group (25-54 years).…”
Section: Discussionsupporting
confidence: 52%
“…Many studies had noted that pathological factors that necessitate completion thyroidectomy includes multifocality, extrathyroidal extension, and some studies also quote the size of the nodule [12,13]. In our study, it was noted that patients with age more than 55 years 6.67 times increased risk of malignancy compared to middle age group (25-54 years).…”
Section: Discussionsupporting
confidence: 52%
“…[ 7 , 9 12 ] The high risk of recurrence in pediatrics distinguishes pediatric DTC from its adult counterpart. One recent study examined DTC patients with a high risk of recurrence with a median age of 43 years and reported a recurrence rate at 10 years of 16.8%, [ 13 ] nearly half the value in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…This result, together with the recurrence pattern, indicates that a degree of occult contralateral PTC led to frequent recurrence in the contralateral thyroid lobe. Indeed, several studies have shown that unilateral multifocality of the primary tumour is an independent predictor of occult contralateral PTC; thus, initial total thyroidectomy or completion thyroidectomy after hemithyroidectomy is recommended in patients with multifocal disease. However, the recurrence rate among patients with multifocal PTC in the present study was only 11 per cent (6 of 57), which would not be enough for initial total thyroidectomy or completion thyroidectomy to be recommended in these patients.…”
Section: Discussionmentioning
confidence: 99%